“Elas são quase da família” - trabalho, identidade e trajetórias de domésticas residentes - Valeriano, Marta Maria (2017)
The dissertation focuses on the work, trajectories and identities of female domestic workers. This paper analyses the work, the trajectories and the migration processes of female domestic workers in which live in their employer's property. It is a case study accomplished in Goiania-GO. The research allied the theoretical foundations of the sociology of work and gender, especially with regard to domestic work, to the theory of identities of Claude Dubar. Methodological practice comprehended quantitative and qualitative investigations, among it: selection and analysis of government databases and semi-structured interviews with thirteen resident domestic workers. Five structural axis were elected under which the analysis were carried out: profile and trajectory, working conditions, daily living in the house of the bosses; identity and recognition. The results reveal that class, race, gender, age and geographical origin intersect and become inequalities in the trajectory of the workers interviewed. Their personal and work trajectories were influenced by the early entry into the labor market through paid domestic work. It was verified that resident domestic workers suffer with extensive working hours and non-compliance with labor laws. According to Girard-Nunes e Silva (2013), it is believed that the condition of being "almost family" personalizes the work relationship, causing subjectivities to interfere in the contractual relationship and in the effectiveness of the rights conquered. The depreciation of the social and occupational identity of resident domestic workers is built and sustained through the devaluation they suffer, both from the state and civil society. Although the law that extends the rights of domestic workers has not yet become effective for the majority of the interviewed, it is recognized as an important achievement and contributes to the deconstruction of the undervalued image of domestic work and domestic workers.